Acceptability of human papillomavirus self-sampling among women living with HIV in sub-Saharan Africa: A systematic review and meta-analysis. - Olunike Rebecca Abodunrin; Folahanmi Tomiwa Akinsolu; Oluwabukola Mary Ola; Mobolaji Timothy Olagunju; Vivienne Ferife; Akim Tafadzwa Lukwa; Ishak Kayode Lawal; George Uchenna Eleje; Oliver Chukwujekwu Ezechi (PLOS Global Public Health)
HPV self-sampling has the potential to improve early detection of cervical cancer among women living with HIV (WLHIV), but its acceptability varies, creating implementation challenges, especially in sub-Saharan Africa. This study aims to assess the acceptability of HPV self-sampling among WLHIV. We searched PubMed, Web of Science, CINAHL, Academic Medical Ultimate, Cochrane databases, and Google Scholar. The review protocol was registered with PROSPERO (CRD42022299781). Inclusion criteria were based on population, intervention, comparison, and outcome. Statistical analysis was done with R Studio version 4.3.2, and data abstraction was performed in Microsoft Excel. The analysis included 14 studies on the acceptability of HPV self-sampling among WLHIV. The overall acceptability rate was 73%. The pooled data showed that 94% felt comfortable with self-sampling, 72% found it easy to use, 10% reported pain, 14% felt embarrassed, and 41% felt confident about the process. The study found that a majority of WLHIV accepted HPV self-sampling, a higher rate than in the general female population. Many participants had concerns about the method's efficacy. This indicates that while WLHIV generally views self-sampling positively, additional education and support are needed to improve their confidence in its accuracy and reliability.